Evaluating the sustained effects of action gaming on visuospatial planning and cognitive flexibility under cognitive fatigue / Muhammad Haiqal Zianuddin ... [et al.]. - Zianuddin, Muhammad Haiqal; Mohd Zaid, Amelia Natasya; Mohd Pozi, Muhammad Ariff Munshir; Mohd Nizam, Muhammad Hariz; Zani, Muhammad Isamuddin; Abu Kassim, Nurul Ain; Mohamed, Muhamad Noor (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study explores the cognitive mechanisms enabling action video game players to maintain problem-solving under cognitive fatigue, addressing gaps in cognitive benefits, causal evidence, and mechanisms. A comparative analysis with non-gamers highlights differences in cognitive resilience and problem-solving performance, offering insights into gaming’s potential role in enhancing cognitive function. This quasi-experimental pre- and post-test study involved 30 participants (n = 30; 18–30 years, Seremban), split into 15 gamers (n = 15; <7 hours gaming per week) and 15 non-gamers (n = 15, <1 hour gaming per week). Cognitive performance was assessed using the Tower of London task pre- and post-intervention, where several values were noted to indicate visuospatial planning and cognitive flexibility. The values noted are average moves and problem-solving time [1]. To induce cognitive fatigue, gamers performed the Stroop test for 45 minutes and non-gamers engaged in a cognitive-neutral activity by watching “NASA’s Cassini Mission” documentary, ensuring controlled intervention contrasts. Paired Sample T-test was conducted afterwards to show effect of time and to differentiate effect between groups, magnitude of mean difference was observed afterwards. Statistical significance was set at (p<0.05).